Bioactive Components in Fermented Foods and Food By-Products - Verardo, Vito (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Food fermentation is one of the most ancient processes of food production that has historically been used to extend food shelf life and to enhance its organoleptic properties. However, several studies have demonstrated that fermentation is also able to increase the nutritional value and/or digestibility of food. Firstly, microorganisms are able to produce huge amounts of secondary metabolites with excellent health benefits and preservative properties (i.e., antimicrobial activity). Secondarily, fermented foods contain living organisms that contribute to the modulation of the host physiological balance, which constitutes an opportunity to enrich the diet with new bioactive molecules. Indeed, some microorganisms can increase the levels of numerous bioactive compounds (e.g., vitamins, antioxidant compounds, peptides, etc.). Moreover, recent advances in fermentation have focused on food by-products; in fact, they are a source of potentially bioactive compounds that, after fermentation, could be used as ingredients for nutraceuticals and functional food formulations. Because of that, understanding the benefits of food fermentation is a growing field of research in nutrition and food science. This book aims to present the current knowledge and research trends concerning the use of fermentation technologies as sustainable and GRAS processes for food and nutraceutical production.